Atwood's reinventions - Howells, Coral Ann (ELOPE (Ljubljana), 2020)
In The Malahat Review (1977), Canadian critic Robert Fulford described Margaret Atwood as "endlessly Protean", predicting "There are many more Atwoods to come". Now at eighty, over forty years later, Atwood is an international literary celebrity with more than fifty books to her credit and translated into more than forty languages. This essay focuses on the later Atwood and her apparent reinvention since 2000, where we have seen a marked shift away from realistic fiction towards popular fiction genres, especially dystopias and graphic novels. Atwood has also become increasingly engaged with digital technology as creative writer and cultural critic. As this reading of her post-2000 fiction through her extensive back catalogue across five decades will show, these developments represent a new synthesis of her perennial social, ethical and environmental concerns, refigured through new narrative possibilities as she reaches out to an ever-widening readership, astutely recognising "the need for literary culture to keep up with the times".
Keywords: Atwood v poznejšem obdobju; Atwood, Margaret; digital technology; digitalna tehnologija; distopija; dystopia; fiction post 2000; later Atwood; pop-proza; popular fiction; proza po letu 2000